2018
DOI: 10.1080/19420862.2018.1553476
|View full text |Cite
|
Sign up to set email alerts
|

Structure, heterogeneity and developability assessment of therapeutic antibodies

Abstract: Increasing attention has been paid to developability assessment with the understanding that thorough evaluation of monoclonal antibody lead candidates at an early stage can avoid delays during late-stage development. The concept of developability is based on the knowledge gained from the successful development of approximately 80 marketed antibody and Fc-fusion protein drug products and from the lessons learned from many failed development programs over the last three decades. Here, we reviewed antibody qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
212
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(214 citation statements)
references
References 360 publications
(421 reference statements)
0
212
0
2
Order By: Relevance
“…The findings indicate leveraging physiochemical charge and hydrophobicity assays as preclinical in vitro tools to filter molecules prior to any in vivo PK assessments are methods to speed the selection and improve the probability of technical success for mAbs. The increased attention and research activity toward the development of in silico and other model-based drug design and selection tools to predict these phenomena for improving druggability within the last few years also reinforces the importance of these factors in affecting nonspecific clearance mechanisms (Mathur et al, 2018;Wolf Pérez et al, 2019;Xu et al, 2019).…”
Section: Molecule-centric Phsiochemical Factors Influencing Dispositimentioning
confidence: 97%
“…The findings indicate leveraging physiochemical charge and hydrophobicity assays as preclinical in vitro tools to filter molecules prior to any in vivo PK assessments are methods to speed the selection and improve the probability of technical success for mAbs. The increased attention and research activity toward the development of in silico and other model-based drug design and selection tools to predict these phenomena for improving druggability within the last few years also reinforces the importance of these factors in affecting nonspecific clearance mechanisms (Mathur et al, 2018;Wolf Pérez et al, 2019;Xu et al, 2019).…”
Section: Molecule-centric Phsiochemical Factors Influencing Dispositimentioning
confidence: 97%
“…Deconvoluted RF-MS spectra for day 14 samples indicated that the primary impurity in low-performing pools (1, 2, 5, 6) was half-antibody. Comparing these pools against the highperforming pools (3,4,7,8) showed a decrease in overall intensity of correctly paired bispecific antibodies as well as an increase in the overall intensity of half-antibodies, which both contribute to the lower percent of correct pair matching. We then analyzed 72 samples from another set of two transfection pools and 16 single cell line clones (four time points each) and characterized the different species identified (Fig.…”
mentioning
confidence: 97%
“…antibody screening | high throughput | intact protein mass spectrometry | electrospray U nambiguous characterization of analytes from complex matrices with high content information in a label-free format continues to expand the application of mass spectrometry (MS) in drug discovery (1)(2)(3). With the need for high accuracy, sensitivity, and selectivity, the rapidly improving MS instrumentations are emerging at the forefront of analyzing analytes with limited alternative assays for biologics developability (4)(5)(6), biotransformation, and high-throughput screening (HTS). For ultra-high-throughput screening, matrix-assisted laser desorption/ionization (MALDI) is amenable to speeds >100,000 samples per day (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…1,2,3 The high cost and long development times, however, present key challenges in the accessibility of monoclonal antibody therapeutics. 4,5 To quickly respond to known and new pathogens and disease, and to provide affordable, high quality treatment to patients around the globe, a molecule must be designed for activity; but it must also be made developable and safe for patients. Adding to their overall cost and process time, many antibodies suffer from poor yields or require individually customized processing protocols or formulations because their biophysical properties cause them to aggregate, unfold, precipitate, or undergo other physical modification during processing into a drug product.…”
Section: Introductionmentioning
confidence: 99%